Applied econometrics & macroeconometric modelling in Nigeria - Adenikinju, Adeola; Busari, Dipo.; Olofin, Sam. (Ibadan : Ibadan University Press, 2009)
The book documents past modelling efforts in Nigeria in a way that will be widely accessible to policy makers, policy advisers and those with research interests on Nigeria.
Includes bibliographic references (587-592) and index
uaj 27/02/2015
Loan
Keywords: Applied Econometrics; Macroeconomtric Modelling; Nigeria